Microarray analysis of circRNAs sequencing profile in exosomes derived from bone marrow mesenchymal stem cells in postmenopausal osteoporosis patients. Issue 1 (19th November 2021) - Fu, Miao; Fang, Liping; Xiang, Xi; Fan, Xijing; Wu, Junqi; Wang, Jinhua
Abstract: Introduction: Bone marrow‐derived mesenchymal stem cells (BMSCs)‐derived exosomes are involved in the modulation of tissue repair and regeneration. CircRNAs play important roles in BMSCs exosomes. The current study sought to explore the role of circRNAs in exosomes derived from BMSCs of postmenopausal osteoporosis (PMOP) patients and the underlying mechanisms. Methods: RNA was extracted from BMSCs exosomes of PMOP and a control group. RNA microarray and bioinformatics analyses were used to explore the expression profile and functions circRNAs. Differentially expressed circRNAs from 20 PMOP and 20 controls were analyzed using RT‐qPCR. Results: A total of 237 upregulated and 279 downregulated circRNAs were identified in the current study. The top‐10 most upregulated circRNAs in the PMOP group were hsa_circ_0069691, hsa_circ_0005678, hsa_circ_0006464, hsa_circ_0015813, hsa_circ_0000511, hsa_circ_0076527, hsa_circ_0009127, hsa_circ_0047285, hsa_circ_0027741, and hsa_circ_0090949. The top‐10 most downregulated circRNAs were hsa_circ_0048669, hsa_circ_0090247, hsa_circ_0070899, hsa_circ_0087557, hsa_circ_0045963, hsa_circ_0090180, hsa_circ_0058392, hsa_circ_0040751, hsa_circ_0067910, and hsa_circ_0049484. RT‐PCR verified dysregulation of 5 circRNAs including hsa_circ_0009127, hsa_circ_0090759, hsa_circ_0058392, hsa_circ_0090247, and hsa_circ_0049484. Moreover, a circRNA‐microRNA‐mRNA interaction network was developed based on differentially expressed circRNAs. Functional analysis showed that pathways involved in the regulation of autophagy, PI3K‐Akt signaling, FoxO signaling, and MAPK signaling were associated with the differentially expressed circRNAs in PMOP patients. Conclusion: The findings of this study show dysregulated circRNAs in BMSCs exosomes of PMOP patients, which may affect the progression of PMOP. These circRNAs can be used as predictive biomarkers and as therapeutic targets for the treatment of PMOP. Abstract : CircRNAs expression patterns. (a) Cluster analysis of circRNAs which are differentially expressed. (b) Volcano plots visualization of relative expression under two conditions. Vertical lines designate 1.5 folds (log2 scaled) up and down, respectively. Horizontal lines represent p ‐value = 0.05 (‐log10 scaled).